PRODUKSI BIBIT KENCUR (Kaempferia galanga L.) MELALUI KULTUR JARINGAN - Lestari, Endang Gati; Hutami, Sri (Research Center for Biology-Indonesian Institute of Sciences, 2005)
To increase domestic and international demand of Kencur (Kaempferia galanga L.) makes this plant potentially develop.Is traditionally used to keep the body warm, as analgetic and expectorant. In the attemp of providing adequately and qualitatively uniformed supply, in vitro experiment has been conducted at BB-Biogen (Indonesian Center for Agricultural Biotechnology and Genetik Resources Research and Development).The selected rhizomes was used as explant. The experiment was orthogonally arranged consisting of MS vitamin and B5, and BA ( 0, 3 and 5 mg/1) and thidiazuron 0,1 mg/1. This experiment comprised three activities, they were shoot initiation, shoot multiplication and acclimatization. The result showed that MS + BA 3 mg/1 + thidiazuron 0,2 mg/1 could induce shoot formation. From the applied media, it was shown that the addition of MS vitamin at the MS basic media and BA 3 and 5 mg/1 added with thidiazuron could result the most optimum shoot, leaves and roots and was not significantly different from the addition of B5 vitamin at basic media of MS + BA 3 and 5 mg/1, 6.9 shoot was averagely produced in this media. The shoot could generate such an adequate number of root that it could be directly acclimatized. The acclimatized plantlet in the green house uses the mixture of soil and manure with the ratio of 1:1 can optimally grow.